An ecological study of the mollusk Lymnaea auricularia near Al-Qabo River mouth - Lattakia Governorate – Syria - Hasan, Dima Husien; Kassab, Mohamed Yacine; Fadel, Ikbal Ahmad (Journal of agricultural, environmental and veterinary sciences, 2022)
The study was conducted on an important freshwater medium near the mouth of the Al-Qabu river, this medium is considered to be significant in terms of its physical and chemical properties, the study was conducted in the period between 07/10/2016 and 27/10/2017, on a basis of twice a month during autumn, spring and summer, and once a month during winter.The species Lymnaea auricularia was studied by collecting 1088 individuals from the mentioned station, where it was found that this species has two main breeding periods, a major one in spring and secondary in autumn, and the life span of the individual is 19 months.The dry weight was estimated by knowing the length of the animal as well as knowing the transverse growth of the shell in terms of longitudinal growth.The station water is mostly of a stinging nature, because that the values ​​of saturation pHs were higher than the measured . and it was also characterized by a high chemical consumption of oxygen > 2 mg/L, especially in autumn and summer. Its high values ​​were associated with a decrease in dissolved oxygen > 6 mg/L. as high values ​​indicate Chemical consumption of oxygen and chlorine ions > 120 mg/L indicates the presence of organic contamination of human origin (sewage).
Keywords: Al-Qabo river; Freshwater mollusks; Gastropods; Population kinetics; Population structure